NUMERACY LITERACY IN ELEMENTARY SCHOOL MATHEMATICS LEARNING - Alman; Almuhaimin Sarnav Ituga (El Midad, 2023)
The purpose of this research is to describe numeracy literacy in elementary school mathematics learning. The approach used is qualitative with a case study in several elementary schools. Data collection in this research involves searching for journals available in various electronic media such as digital libraries, the internet, through Google Scholar. The results of the numeracy literacy analysis indicate that students' numeracy literacy skills involve three main components. Firstly, students need to have skills in understanding and using mathematical symbols and numbers in various contexts. Secondly, students should be able to analyze information presented in various visual forms, such as graphs and tables. Thirdly, students also need to have the ability to solve mathematical problems that involve the use of numbers and symbols. The implications of this research can be used as a foundation for the development of a more inclusive and contextual mathematics curriculum, as well as to assist teachers in designing effective learning strategies to enhance students' numeracy literacy.